Analysis of Student Learning Styles and Implementation of Relevant Learning Methods to Optimize the Teaching and Learning Process - Anwari, Annisa' Fitriyah; Bahar Agus Setiawan (Program Pascasarjana Universitas Ibrahimy, 2025)
The purpose of this research is to map the learning styles of students so that they can be found in 1 class what learning styles are owned by students and what learning methods are suitable for their learning styles. The method used is a mix method by combining the quantitative method of distributing questionnaires to identify students' learning styles and qualitative methods to describe learning methods that are suitable for each existing learning style. The results of this study show that there are 4 learning styles, namely visual, auditory, kinesthetic and mixed (auditory visual and visual kinesthetic). Learning methods that can be used for visual learning styles are: Learning videos, concept maps (Mind Mapping) and Visual presentations. For auditory learning style methods, namely: Class discussions and debates, podcasts and audio recordings and interactive lectures. For kinesthetic learning style methods, namely: Project-Based Learning, simulation and role-playing and field practice. And for mixed learning styles, namely: 1) visual auditory learning styles using multimedia presentation methods and interactive webinars. 2) the kinesthetic visual learning style uses 3D model and simulation methods and practical demonstrations.